2021
DOI: 10.1183/16000617.0161-2021
|View full text |Cite
|
Sign up to set email alerts
|

Smouldering fire or conflagration? An illustrated update on the concept of inflammation in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a rare condition that is characterised by a progressive increase of pulmonary vascular resistances that leads to right ventricular failure and death, if untreated. The underlying narrowing of the pulmonary vasculature relies on several independent and interdependent biological pathways, such as genetic predisposition and epigenetic changes, imbalance of vasodilating and vasoconstrictive mediators, as well as dysimmunity and inflammation that will trigger endothelial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
6
0
3
Order By: Relevance
“…In addition, in accordance with our results, previous studies have shown that oxidative stress and ROS trigger NGF expression from various cell types [ 24 , 25 , 26 , 27 ]. Inflammation is a critical PH pathophysiological feature [ 6 , 10 , 11 ], with increased expression of numerous pro-inflammatory cytokines such as IL-1β [ 35 , 36 , 37 ]. The source of increased IL-1β in PH may include both infiltrated inflammatory cells [ 38 ], such as in particular macrophages [ 39 ], but also pulmonary arterial structural cells such as hPASMC and hPAEC [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in accordance with our results, previous studies have shown that oxidative stress and ROS trigger NGF expression from various cell types [ 24 , 25 , 26 , 27 ]. Inflammation is a critical PH pathophysiological feature [ 6 , 10 , 11 ], with increased expression of numerous pro-inflammatory cytokines such as IL-1β [ 35 , 36 , 37 ]. The source of increased IL-1β in PH may include both infiltrated inflammatory cells [ 38 ], such as in particular macrophages [ 39 ], but also pulmonary arterial structural cells such as hPASMC and hPAEC [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously shown that both PASMC and PAEC express NGF [ 5 , 9 ]. Inflammation, a critical PH pathological feature [ 10 , 11 , 12 ], can trigger NGF secretion from different cell types outside the lung, for example, urothelial cells [ 13 ], synovial fibroblasts [ 14 ], chondrocytes [ 15 ], or various cells of the gastrointestinal tract [ 16 , 17 , 18 ]. Inflammation can also increase NGF expression in the lung, for example in pulmonary fibroblasts [ 19 ], bronchial epithelial [ 20 ] or smooth muscle cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…REVUES gine de ces transformations ne sont pas entièrement élucidés. Plusieurs processus physiopathologiques sont impliqués (Figure 4), tels que la dysfonction endothéliale, la migration et la prolifération de cellules musculaires lisses et de cellules endothéliales des artères pulmonaires, la transition endothélio-mésenchymateuse, la prolifération, la migration et la différenciation accrues des fibroblastes adventitiels de l'artère pulmonaire, l'inflammation, l'hypoxie, les dommages à l'ADN, et le stress oxydant [5,12,13].…”
Section: Synthèseunclassified
“…de ces caractéristiques inflammatoires et dysimmunitaires font encore l'objet de discussions enflammées [12]. Néanmoins, les mutations les plus importantes qui ont été associées à l'HTAP touchent des gènes qui jouent un rôle critique dans les mécanismes de régulation de la réponse immunitaire, en plus de leur importance dans l'homéostasie et dans la fonction vasculaires [12].…”
Section: Revuesunclassified
“…PAH is characterized by excessive pulmonary vascular remodeling, which involves medial hypertrophy—an early event in PAH and even reversible, appearing in all PAH subgroups -, proliferative and fibrotic changes of the intima, adventitious thickening, and thrombosis in situ ( 1 3 , 8 11 ). The mechanisms behind these transformations are not fully understood ( 12 )—several pathophysiological processes are entailed, such as migration and proliferation of pulmonary arterial smooth muscle cells (PASMCs) and endothelial cells (ECs) ( 1 , 2 ), endothelial dysfunction, endothelial-to-mesenchymal transition ( 13 ), enhanced adventitial pulmonary artery fibroblast proliferation, migration, and differentiation ( 14 ), inflammation ( 15 , 16 ) and oxidative stress ( 2 , 3 , 8 , 9 ). Particularly, ECs may be involved in synthesizing growth factors that stimulate non-cellular matrix deposition and smooth muscle hypertrophy, contributing to the formation of plexiform lesions ( 1 , 4 , 10 , 17 ).…”
Section: Introductionmentioning
confidence: 99%